Ichthyofauna checklist (Chordata: Actinopterygii) for indicating water quality in Kampar River catchment, Malaysia - CASEY KEAT-CHUAN NG; PETER AUN-CHUAN OOI, WEY-LIM WONG; GIDEON KHOO (Biodiversitas Journal of Biological Diversity, 2018)
Ng CKC, Ooi PAC, Wong WL, Khoo G. 2018. Ichthyofauna checklist (Chordata: Actinopterygii) for indicating water quality in Kampar River catchment, Malaysia. Biodiversitas 19: 2252-2274. The limnological habitats are receptors of pollution, thus local fish species richness is a plausible biological indicator to reflect the quality of a particular water body. However, database on species occurrence that corresponds with the water physico-chemistry constituents is often not available. The problem is compounded by the lack of species identification description to assist those working on river and freshwater resource conservation projects. This paper attempts to fill the gaps in the context of Kampar River drainage. Based on sampling exercises conducted from October 2015 to March 2017, an annotated list with visual data for 56 species belonging to 44 genera and 23 families is presented. The water physico-chemistry data is also summarized with the corresponding visual data of limnological zones studied. The species diversity results are further compared with other local drainages and the correlation between area size and their relationship is expressed by y = 17.627e0.0601x. This paper provides species-level identification information for front line practice and demonstrates how the fish taxonomy discipline can be adapted for practical application in freshwater resource monitoring and management.